Who Becomes an Unwed Mother in Greece? Sociodemographic and Geographical Aspects of an Emerging Phenomenon. Issue 3 (10th January 2013) - Gavalas, Vasilis S.; Rontos, Kostas; Salvati, Luca
ABSTRACT Out of all European countries, the one with the lowest rate of childbearing outside marriage is Greece. However, it seems that the traditional attitudes towards family formation and childbearing have begun to change in Greece as well. Illegitimacy ratio has increased fourfold in less than 30 years. It is by using the vital statistics provided by the National Statistical Service of Greece that this paper answers to research questions regarding the sociodemographic profile of unwed mothers in Greece, in terms of educational level, age, and nationality. It also tries to find out what are the reasons of non‐marital childbearing in Greece and to investigate the geographical variation of this phenomenon within the country. A key finding is that the rise in the illegitimacy ratio from the 1990s onwards is largely due to the inflow of immigrants from other countries, mostly from the former Eastern Bloc. The social profile of these unwed mothers is totally different from their Greek counterparts, implying that foreign nationals who have children outside marriage do so by conviction and not because an unwanted pregnancy resulted to birth, which is mostly the case with Greek unwed mothers. Copyright © 2013 John Wiley & Sons, Ltd.